2015
DOI: 10.11648/j.acm.20150405.18
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Increasing Input Costs to the Farmers in Cotton Production in Tanzania

Abstract: The persistence of increasing input costs has effects to the farmers in the process of cotton production. These input costs can be in terms of pesticides, seeds, fertilizers, sprayers and the like, that have a real contribution towards cotton outputs per hectare. This paper intended to analyze effects of increasing input costs to the cotton farmers in Tanzania. The primary data were collected through questionnaires, which were distributed to 35 respondents, who are knowledgeable enough about cotton production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It is agreeing with Hina et al (2004), they concluded that prices of cotton influence on production and cultivated area, which is also confirmed from finding of Guillham et al (1995) as well. Cultivated area, production and price are interrelated, raising of prices of cotton support to extend of cultivated area by encouraging farmers, ultimately production, but situation is different, during survey, we found that farmers complain about day-by-day raising of cultivation cost and low rate of cotton, this factor should not be avoided in the policy management, since, great variation for the cultivated area seen in different UCs, In this support, we have reference of Dome et al (2015) said that input cost has negative effect on farmers in the cotton cultivation progress, such as cost of cultivation, like sowing, fertilizer, seed, (Nabi, 1991) and damagingly affect profit ( Ahmed et al, 2016).…”
Section: Discussionmentioning
confidence: 74%
“…It is agreeing with Hina et al (2004), they concluded that prices of cotton influence on production and cultivated area, which is also confirmed from finding of Guillham et al (1995) as well. Cultivated area, production and price are interrelated, raising of prices of cotton support to extend of cultivated area by encouraging farmers, ultimately production, but situation is different, during survey, we found that farmers complain about day-by-day raising of cultivation cost and low rate of cotton, this factor should not be avoided in the policy management, since, great variation for the cultivated area seen in different UCs, In this support, we have reference of Dome et al (2015) said that input cost has negative effect on farmers in the cotton cultivation progress, such as cost of cultivation, like sowing, fertilizer, seed, (Nabi, 1991) and damagingly affect profit ( Ahmed et al, 2016).…”
Section: Discussionmentioning
confidence: 74%